Exploring the value of academic libraries in the 21st century: a comparative study of two universities in Southern Africa - Malapela, Thembani (Department of Knowledge and Information Stewardship, 2025)
The concept of providing evidence of the value or worth of an academic library service has concerned librarians for more than five decades. Discourse on the value of libraries was stimulated in the United States by budgets and resource allocations in higher education institutions. Performance measurement sought to assess and justify the services offered in terms of the needs of stakeholders: politicians, higher education administration, students and parents. This development challenged the long-held notion that the academic library was the heart of the university. To remain appreciated and funded, academic libraries were now required to provide empirical evidence that they added value for their stakeholders and supported the mandates of the institutions that house them. This study explores and interrogates the value of academic libraries in the face of the changing demands of Higher Education – stakeholders and users – in two academic libraries in Southern Africa. The study sought to establish the extent to which the respective academic library services can be perceived to add value for their users. The study employed the comparative case study research methodology and used three research instruments –documentary analysis, interviews and questionnaires – to collect data in institutions in Zimbabwe (Institution A) and South Africa (Institution B). At the request of the institutions, their identities remain confidential. Value like beauty, it lies in the eyes of the beholder, and economists, sociologists, psychologists and marketers all have a different concept of value. This study investigated value from the point of view of value-in-use, a theoretical approach introduced by Adam Smith in his original attempt to define economic value .This approach was refined in Library and Information Science literature by Saracevic and Kantor's (1997) theorising of the use-oriented value of library and information services. The data collected was subjected to a two-pronged analysis: the first was based on the research questions and the second was informed by an original theoretical framework. This framework enabled a taxonomy that produced a checklist for four elements of academic library value chosen for the study –student learning, student success, faculty teaching and researcher productivity. The findings of the study indicate that both libraries were aligned with their institutional mission, vision and goals. While the libraries offered services that support the fulfilment of their institutional mandates, using the results of the four elements of value as a sample of all value elements, there was a need for them to design services that meet specific expected outcomes for both students and academics. The main conclusion was that academic libraries continue to contribute to the mission and strategic goals of the institutions that house them. To remain an asset to the university, libraries should demonstrate their value within their institutional context by strategically aligning with the institutional mandate and linking their outcomes to elements of value (such as student success, teaching and research productivity). Despite major environmental changes in Higher Education, both technological and economic, academic libraries are appreciated and used by both students and staff. Both user groups indicated that the academic library's closure would seriously harm both the researchers' work and the students' access to information. The “Taxonomy of Value in Academic Libraries”, which was developed in this study, appears to be a necessary tool to assess elements of value in academic libraries and should be further developed.